Fool's gold? A critical assessment of sources of data on heritage crime. Issue 1 (27th November 2018) - Grove, Louise; Thomas, Suzie; Daubney, Adam
Abstract : Purpose: The purpose of this paper is to explore critically various sources of data available on heritage crime, and consider how these may be utilised and improved. Design/methodology/approach: This study is primarily a scoping review of the current heritage crime data climate, embedding examples from a range of existing and potential information sources. It highlights opportunities to improve data resources. Findings: A lack of consistency in reporting and recording practices means there is little meaningful evidence about heritage crime trends and patterns. This needs to change in order to develop and evaluate appropriate strategies to reduce the problem of heritage crime nationally and internationally. Research limitations/implications: It is hoped that urging improvement of data resources in the heritage crime sector will inspire a greater number of researchers to analyse and address key problems within heritage crime. Practical implications: This paper encourages the development of new and improved data collection methods to foster effective assessment of existing heritage crime reduction schemes and better support victims of heritage crime. Social implications: Increasing availability and accessibility of high-quality data on heritage crime would allow for developing better protections and resource allocation for vulnerable heritage. Originality/value: This paper has drawn together, for the first time, evidence of the existing state of affairs of data availability within heritage crime. It is a position paper which encourages the development of improved recording and reporting practices both formally and informally across heritage and criminal justice sectors in order to support further research and understanding of the heritage crime problem.